Application of a novel hybrid MIL-53(Al)@rice husk for the adsorption of glyphosate in water: Characteristics and mechanism of the process. (June 2023) - Zambrano-Intriago, Luis Angel; Daza-López, Erlinjka Valentina; Fernández-Andrade, Alex; Luque, Rafael; Amorim, Célia G.; Araújo, Alberto N.; Rodríguez-Díaz, Joan Manuel; Montenegro, Maria C.B.S.M.
Abstract: The development of new materials that have a high capacity to remove pollutants in water-based media is becoming increasingly important because of the serious contamination of water and the negative impact on biodiversity and public health. The presence of glyphosate in water, the most widely used herbicide worldwide, has triggered alerts owing to the collateral effects it may cause on human health. The main objective of the present study was to investigate the potential of the hybrid material MIL-53(Al)@RH for the adsorption of glyphosate in aqueous solution. The material was obtained following the methodology of MIL-53(Al) synthesis in the presence of hydrolyzed rice husk assisted by microwave. Batch adsorption experiments were carried out to evaluate the adsorbent dosage, pH0 solution effect, contact time, adsorbate concentration, and temperature effect. The results demonstrated that a maximum adsorption capacity of 296.95 mg g −1, at pH0 4 with a ratio of 0.04 g MIL-53(Al)@RH/50 mL of solution, was achieved in 30 min. The Avrami and pseudo-second order models appropriately described the adsorption kinetics and the equilibrium by Langmuir and Sips models. The enthalpy changes (ΔH°) determined propose an endothermic reaction governed by chemisorption, corroborating the kinetic and equilibrium settings. Hydrogen bonds, π*-π interactions, and complexation between the metal centers of MIL-53(Al) and the anionic groups of glyphosate were postulated to be involved as adsorption mechanisms. Finally, for practical application, MIL-53(Al)@RH was packed in a column for a fixed-bed test which revealed that the hybrid can remove glyphosate with an adsorption capacity of 76.304 mg L −1, utilizing 90% of the bed. Graphical abstract: Image 1 Highlights: MIL-53(Al)@RH layered hybrid synthesized by microwave assistance. This adsorbent showed an adsorption capacity of 296.95 mg g −1 for glyphosate. Hydrogen bonds, π*-π interactions, and complexes were the main mechanisms. Proposed column system.